CONSECUTIVE TRANSLATION - Ahmedova Mahliyo; Qambaraliyeva Durdona Nodirbek's kizi; Kobulova Mahliyo Kodirjon kizi; Habibullayeva Madina Yorbek kizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: whether interpreting in simultaneous or consecutive mode, we’re thankful for all of the interpreters who help us communicate!